Antigen Presentation and MHC Class II Expression by Human Esophageal Epithelial Cells: Role in Eosinophilic Esophagitis - Mulder, Daniel J. (American Society for Investigative Pathology, 2011)
Professional antigen-presenting cells (APCs) play a crucial role in initiating immune responses. Under pathological conditions, epithelial cells at mucosal surfaces act as nonprofessional APCs, thereby regulating immune responses at the site of exposure. Epithelial cells in the esophagus may contribute to the pathogenesis of eosinophilic esophagitis (EoE) by presenting antigens on the major histocompatibility complex (MHC) class II. Our goal was to demonstrate the ability of esophageal epithelial cells to process and present antigens on the MHC class II system and to investigate the contribution of epithelial cell antigen presentation to EoE. Immunohistochemistry detected HLA-DR, CD80, and CD86 expression and enzyme-linked immunosorbent assay detected interferon-γ (IFNγ) in esophageal biopsies. Antigen presentation was studied using the human esophageal epithelial cell line HET-1A by reverse transcriptase-PCR, flow cytometry, and confocal microscopy. T helper cell lymphocyte proliferation was assessed by flow cytometry and IL-2 secretion. IFNγ and MHC class II were increased in mucosa of patients with EoE. IFNγ increased mRNA of HLA-DP, HLA-DQ, HLA-DR, and CIITA in HET-1A cells. HET-1A engulfed cell debris and processed ovalbumin. HET-1A cells expressed HLA-DR after IFNγ treatment. HET-1A stimulated T helper cell activation. In this study, we demonstrated the ability of esophageal epithelial cells to act as nonprofessional APCs in the presence of IFNγ. Esophageal epithelial cell antigen presentation may contribute to the pathophysiology of eosinophilic esophagitis.